2010
DOI: 10.1097/aud.0b013e3181d3d4f3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Noise, Nonlinear Processing, and Linear Filtering on Perceived Speech Quality

Abstract: The data reported here provide a comprehensive dataset of speech quality ratings for simulated hearing aid processing conditions. The results indicate that quality ratings by listeners with hearing loss are significantly lower than quality ratings by listeners with normal hearing. In addition, quality ratings by listeners with hearing loss are impacted by signal processing at least as much as, and often more than, the quality ratings by listeners with normal hearing. Finally, quality ratings for speech process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…Given the literature on the relationship between conjoint analysis and rating scales for measuring preferences (Johnson et al, 2006;Phillips et al, 2002;Ryan et al, 2001), we hypothesized that there would be differences between the two methods in assessing hearing aid preferences (Arehart et al, 2010;Fitzpatrick et al, 2007;Meister et al, 2001;Moeller et al, 2009). This was not in fact the case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the literature on the relationship between conjoint analysis and rating scales for measuring preferences (Johnson et al, 2006;Phillips et al, 2002;Ryan et al, 2001), we hypothesized that there would be differences between the two methods in assessing hearing aid preferences (Arehart et al, 2010;Fitzpatrick et al, 2007;Meister et al, 2001;Moeller et al, 2009). This was not in fact the case.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kochkin (2007) utilizes a 7-point Likert scale in assessing a variety of dimensions of satisfaction. Other examples of Likert or ratings scales include Bagatto et al (Bagatto, Moodie, Seewald, Bartlett, & Scollie, 2011), Arehart et al (Arehart, Kates, & Anderson, 2010), and Moeller et al (Moeller, Hoover, Peterson, & Stelmachowicz, 2009). Conjoint analysis utilizes pairwise comparisons to estimate preferences (Thurstone, 1929).…”
mentioning
confidence: 99%
“…For instance, Gabrielsson and Sjögren (1979) did an experiment in which participants had to describe the sound of eight different headphones. They found that the headphone with a 10-dB peak in the frequency response at 3 kHz scored strongly on adjectives related to "sharp/hard/loud" and on (Arehart, Kates, & Anderson, 2010) and can improve the threshold of discomfort (Warner & Bentler, 2002). …”
Section: Introductionmentioning
confidence: 99%
“…Speech quality is affected by factors such as noise and distortion (Kates and Kozma-Spytek, 1994;Arehart et al, 2010). The addition of background noise (e.g., babble noise and machine noise) often leads to deterioration in speech quality (Ramirez et al, 2008;Arehart et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of background noise (e.g., babble noise and machine noise) often leads to deterioration in speech quality (Ramirez et al, 2008;Arehart et al, 2010). The amount of noise is quantified in terms of the signal-to-noise ratio (SNR).…”
Section: Introductionmentioning
confidence: 99%